Acoapetaludines A-K, C20 and C19-diterpenoid alkaloids from the whole plants of Aconitum apetalum (Huth) B.Fedtsch. (November 2019) - Hu, Zhan-Xing; An, Qiao; Tang, Hong-Yu; Chen, Zheng-Hong; Aisa, Haji Aker; Zhang, Yu; Hao, Xiao-Jiang
Abstract: A C20 -diterpenoid alkaloid with an unprecedented carbon skeleton, acoapetaludine A, together with ten undescribed aconitine-type C19 -diterpenoid alkaloids, acoapetaludines B–K, were isolated from the whole plants of Aconitum apetalum (Huth) B. Fedtsch. (Ranunculaceae). The structures were elucidated based on a comprehensive spectroscopic data analysis. The absolute configuration of acoapetaludine A was determined by quantum ECD calculation. Acoapetaludines D and E exhibited weak anti- Helicobacter pylori activity at a minimum inhibitory concentration (MIC) of 100 and 50 μg/mL, respectively. Graphical abstract: Eleven undescribed C20 and C19 -diterpenoid alkaloids were isolated from the whole plants of Aconitum apetalum (Huth) B. Fedtsch. Two of them exhibited weak anti- Helicobacter pylori activity at MICs of 100 and 50 μg/mL, respectively. Image 1 Highlights: Eleven undescribed C20 and C19 -diterpenoid alkaloids were isolated from the whole plants of Aconitum apetalum . Acoapetaludine A possessed an unprecedented carbon skeleton. The absolute configuration of acoapetaludine A was determined by quantum ECD calculation. The anti- Helicobacter pylori activities of the isolates were evaluated.